Haemolytic–uraemic syndrome with bacteraemia caused by a new hybrid Escherichia coli pathotype. Issue 4 (27th May 2014) - Mariani‐Kurkdjian, P.; Lemaître, C.; Bidet, P.; Perez, D.; Boggini, L.; Kwon, T.; Bonacorsi, S.
Abstract We describe a new atypical Shiga‐toxin‐producing Escherichia coli (STEC) responsible for a severe episode of haemolytic–uraemic syndrome in an adult with a relapse associated with bacteraemia. This STECs train of serotype O80:H2 harboured stx2c and stx2d gene subtypes, the rare eae ξ variant and a ColV plasmid with a conserved virulence plasmidic region involved in virulence of human and avian extraintestinal pathogenic E. coli. This atypical hybrid pathotype, which represents a new threat, is a further demonstration that STEC may be a recipient for extraintestinal virulence factors and raises again the question of antibiotic therapy during STEC infection.